Therapeutic chemonucleolysis of the lumbosacral disk in a cadaveric model: lateral vs sternal technique. (International Journal of Health, Animal Science and Food Safety, 2016)
The widespread use of advanced Imaging techniques has dramatically improved the diagnosis of caudaequina syndrome in geriatric small animal patients. Two different techniques (sternal vs lateralrecumbency) were tested in twelve cadavers for the L7-S1 disk injection under fluoroscopic guidance.Twelve dogs were enrolled in the study: eight intervertebral lumbosacral disks were injected with agelatinous radiopaque compound and the remnants four disks with an alcoholic radiopaque solution.The dogs were randomly positioned either in lateral recumbency with the lumbo-sacral joint in neutralposition (six dogs), or in sternal recumbency with the hind limbs extended cranially along the body andthe lumbosacral joint flexed (six dogs). The correct injection of the compounds within the lumbosacraldisk was checked both by computed tomography (CT) and gross anatomic examination. The lateraltechnique required less time of execution and minor attempts for the correct positioning of the needle.All the injected disks were visible on CT, while necroscopy resulted satisfactory only in five patients.Leakage of the compounds outside the disk was observed in two cases. The percutaneous injection inlateral recumbency under fluoroscopic guidance resulted rapid and feasible in a cadaveric model. Futureclinical trials are required to assess the safety of chemonucleolysis in diseased patients.
Keywords: chemonucleolysis; lumbosacral disk; fluoroscopy; cauda equine syndrome